(untitled) (Research, Society and Development, 2022)
The study of this work was analyzed as hardships felt by patients, proceed with the request for a health objective, specifically requesting the performance of robotic radical prostatectomy, the total withdrawal of the use of robotic surgery as a means of improving the patient’s quality of life. A preamble is made about prostate cancer, the second most prevalent cancer among men in Brazil (INCA, 2022). Robotics is performed through minimally invasive procedures, using robotic instruments for the treatment of robotic conditions in which the operation is already operating and the safety of the operation. About cancer arising in men and the possibility of a better quality of life for the patient with the use of this therapy indicated by several doctors listed in the Brazilian Society of Urology, behold, thousands of holders of various health plans have administratively denied the quality of specialist doctors for robotic surgeries, given the pathologies inherent to each request, which pathologies are covered when contracting the plan. Federal Supreme Court precedents and Federal doctrinal understandings that defend that Consumer Defense acts must comply with the Constitution and the Consumer Defense Code, and cannot innovate the legal order. On these occasions, the writ of mandamus is the legal remedy and is provided for in the best 5th, item LXIX, of the Federal Constitution, being disciplined by Law No. 12.016/2009. It is intended to protect the offended’s net and right.